Finding Women in the University Archives: Women’s Scholarships and Their Impact on the Early Modern University - Morrison, Claire (Early Modern Low Countries, 2025)
This article explores the overlooked involvement of women in supporting the University of Leuven during the sixteenth and seventeenth centuries. Despite gendered regulations against the presence of women in early modern universities, archival evidence reveals their significant roles in providing scholarships to students. Through detailed analysis of testamentary records, the study uncovers women’s deep engagement with the university’s activities. Spanning various social backgrounds, these women demonstrated a profound understanding of the university’s operations and influenced its development through financial support and by designing instructions for student conduct and academic focus. Despite often being sidelined in historical narratives, their contributions challenge traditional views of male-dominated academia and underscore the diverse roles women played in shaping early modern universities.